Applying the Population Health Standard to the Regulation of Electronic Nicotine Delivery Systems. Issue 5 (22nd September 2020) - Cahn, Zachary; Drope, Jeffrey; Douglas, Clifford E; Henson, Rosemarie; Berg, Carla J; Ashley, David L; Eriksen, Michael P
Abstract: Regulatory authorities have devoted increasing attention and resources to a range of issues surrounding the regulation of novel nicotine and tobacco products. This review highlights the inherent complexity of evaluating prospective policies that pertain to products that heat solutions containing nicotine, but not tobacco leaf, sometimes referred to as electronic nicotine delivery systems (ENDS). The US Food and Drug Administration (FDA) is compelled to incorporate a set of public health criteria in their decision making, collectively referred to as the Population Health Standard. Adherence to this standard is necessary to estimate the impact of prospective ENDS policy decisions on net population harm associated with nontherapeutic nicotine products. For policies that are expected to decrease or increase ENDS use, application of the Population Health Standard requires a comprehensive assessment of the status quo impact of ENDS use on population health. Accordingly, this review first assesses the state of the evidence on the direct harms of ENDS and the indirect effects of ENDS use on smoking, particularly rates of initiation and cessation. After that, the example of flavor restrictions is used to demonstrate the further considerations that are involved in applying the Population Health Standard to a prospective ENDS policy. Implications: This narrative review aims to inform regulatory considerations about ENDS through the prism of the Population Health Standard. More specifically, this review (1) describes and explains the importance of this approach; (2) provides guidance on evaluating the state of the evidence linking ENDS to the net population harm associated with nontherapeutic nicotine products; and (3) illustrates how this framework can inform policymaking using the example of flavor restrictions.